2010
DOI: 10.1016/j.envint.2009.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic and naturally-produced organobrominated compounds in marine mammals from Brazil

Abstract: Liver samples from 51 cetaceans, comprising 10 species, stranded between 1994 and 2006 in a highly industrialized and urbanized region in Southeast Brazil, were analyzed for polybrominated diphenyl ethers (PBDEs) and methoxylated-PBDEs (MeO-PBDEs). A concentration range of PBDEs (3-5960 ng/g lw) similar to that observed in Northern Hemisphere dolphins was found. MeO-PBDE concentrations in continental shelf (CS) dolphins from Brazil are among the highest detected to date in cetaceans (up to 250 µg/g lw). Higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
52
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(65 citation statements)
references
References 53 publications
8
52
0
5
Order By: Relevance
“…The concerns generated by the DRC contamination are amplified when it is taken into account that these cetaceans are exposed to other persistent bioaccumulative toxicants (PBTs) that have been shown to be endocrine disrupters, tumor promoters and immunosuppressors as well (Schecter et al, 2006;Simonyte et al, 2006;Sonne et al, 2006a;Whalen et al, 1999). The high exposure of cetaceans from Brazil to cadmium (Dorneles et al, 2007a(Dorneles et al, , 2007b, mercury (Lailson-Brito et al, 2012a), organochlorine pesticides (Lailson-Brito et al, 2011, 2010, 2012b, as well as to organotin (Dorneles et al, 2008b), perfluoroalkyl (Dorneles et al, 2008a) and organobrominated (Alonso et al, 2012;Dorneles et al, 2010) compounds has already been reported. Therefore, the possibility of synergistic effects among these PBTs should not be ruled out.…”
Section: A Serious Pcb Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…The concerns generated by the DRC contamination are amplified when it is taken into account that these cetaceans are exposed to other persistent bioaccumulative toxicants (PBTs) that have been shown to be endocrine disrupters, tumor promoters and immunosuppressors as well (Schecter et al, 2006;Simonyte et al, 2006;Sonne et al, 2006a;Whalen et al, 1999). The high exposure of cetaceans from Brazil to cadmium (Dorneles et al, 2007a(Dorneles et al, , 2007b, mercury (Lailson-Brito et al, 2012a), organochlorine pesticides (Lailson-Brito et al, 2011, 2010, 2012b, as well as to organotin (Dorneles et al, 2008b), perfluoroalkyl (Dorneles et al, 2008a) and organobrominated (Alonso et al, 2012;Dorneles et al, 2010) compounds has already been reported. Therefore, the possibility of synergistic effects among these PBTs should not be ruled out.…”
Section: A Serious Pcb Problemmentioning
confidence: 99%
“…Rough-toothed dolphins and false killer whales occur in tropical to warm temperate waters all over the world (Baird, 2009;Miyazaki and Perrin, 1994). In Brazil, these species occur predominantly on the continental shelf (Bisi, 2011;Dorneles et al, 2010Dorneles et al, , 2008bDorneles et al, , 2007a and rough-toothed dolphins can even be found in shallow coastal waters (Flores and Ximinez, 1997). Rough-toothed dolphins can occasionally reach more than 2.8 m of total length (Jefferson, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Iron is another element that can regulate phytoplankton growth and composition since it can determine nitrogen and silicate incorporation (DUGDALE; WILKERSON, 1998;HUTCHINS;BRULAND, 1998). Miller (2004) has suggested that iron limits the size of phytoplankton.…”
Section: Physical-biological Interactions: Ecological Consequences Ofmentioning
confidence: 99%
“…A ocorrência de BFRs em amostras ambientais da costa brasileira evidencia o uso desses produtos no Brasil. 39,110,122,124,129,131,134 Portanto, é fundamental que este tema seja abordado com maior propriedade, por meio de estudos que permitam uma avaliação detalhada do status da contaminação atual e futura, bem como pela implementação de legislações específicas no país.…”
Section: Considerações Finaisunclassified